Design and build a mechanical energy conservation law KIT with Arduino microcontroller - Adina Widi Astuti; Zayyinul Mushthofa; Sulhadi Sulhadi (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2021)
Tools as media play an important role in learning physics to explain concepts, so that students can more easily build mastery of physics material and develop their skills. This study aims to design and realize a physics learning tool. The method used is research and development (Research and Development). This learning tool is in the form of a plane where the direction of the object's trajectory varies can move up, down, and is accompanied by a slope setting (30˚, 45˚, 60˚ or 90˚). Equipped with a speed output setting program based on 3 points whose speed will be measured and the distance between the points can be changed. Its function is to understand and prove the law of conservation of mechanical energy, understand the relationship between potential energy and kinetic energy experienced by objects and determine the speed of objects and their height position. This learning tool is expected to attract students' interest in learning physics. The design of this KIT Law of Conservation of Mechanical Energy can prove the conservation of mechanical energy. When an object is moving downwards, the object's height decreases but its velocity increases. On the other hand, if the object is moving upwards, the height of the object will increase, but the velocity of the object will decrease. This tool still has a relative error rate of 23.92% in free fall motion, 31.87% in falling motion on an inclined plane, and 32.79% in vertical upward motion.©2021 JNSMR UIN Walisongo. All rights reserved.